Impact of Updated Curriculum Content on 6th-7th Graders’ Motivation in Physical Education - Prystynskyi, Volodymyr; Babych, Vjacheslav; Zaytsev, Volodymyr; Boychuk, Yurij; Taymasov, Yurij (Physical Education Theory and Methodology, 2020)
The purpose of the study was to determine the impact of updated curriculum content on 6th-7th graders’ motivation in physical education. Materials and Methods. The study participants were 457 6th-7th graders from different regions of Ukraine (n = 230 girls and n = 227 boys). To determine the impact of curriculum content on school students’ motivation in physical education, the study used methods of theoretical analysis, systematization, comparison, generalization, pedagogical observations, questionnaire, mathematical statistics. Results. The study found that the content of 2012-2017 curricula has significant advantages in terms of developing school students’ motivation for regular exercise. The impact results in a statistically significant increase in indicators of the school students’ choice of learning motive (8.5% more; t = 2.24; p ≤ 0.05-0.01), evaluation motive (5.0% more; t = 2,01; p ≤ 0.05), play motive (6.3% more; t = 2.07; p ≤ 0.05). The study determined an increase in the high level of learning motivation from 14 to 33 cases and in the above average level – from 21 to 48, as well as a decrease in the average level – from 59 to 56, the reduced level – from 21 to 17, and the low one – from 12 to 11 cases. Conclusions. It was found that the result of the impact on school students’ motivation in physical education is the inclusion of new components into curricula. It was defined that an increase in motivation is associated, first, with the inclusion of content lines “Environmental Safety and Sustainable Development”, “Civil Responsibility”, “Health and Safety”; secondly, sections “Theoretical and Methodological Knowledge” and “Expected Results of Educational and Cognitive Activity”; thirdly, a modular system of organizing the educational process; fourth, sections “Evaluation of Learning Achievements” and “Homework”. The result of the impact of updated curriculum content is the enhancement of school students’ motivation in physical education, first of all through educational (cognitive) and social motives.